Preparation And Optimisation Of Valsartan Bilayered Sustained Release Matrix Tablets - Soumya, M (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT The purpose of the present investigation was to develop and optimize bilayered sustained release matrix tablets of Valsartan. The tablets contained an immediate releasing layer with the loading dose of the drug and a sustaining layer with maintenance dose of drug prepared by wet granulation method. The immediate releasing layer is directly compressed on to the sustaining layer. Sodium starch glycholate was used as super disintegrant and Eudragit RSPO and Eudragit RLPO were used as polymers. The drug polymer interaction was investigated by FTIR and DSC and their results directed further course of formulation. Valsartan tablets were evaluated for various post compression parameters like Tablet hardness, Friability, Weight variation, Drug content and In vitro dissolution. The results were found to be within the acceptable limits. A 32 full factorial design was applied to systematically optimize the drug release profile. The amounts of Eudragit RSPO (X1) and Eudragit RLPO (X2) were selected as independent variables. The time required for 90% (t90%) drug dissolution was selected as dependent variable. The formulations F1 to F4 showed that the drug release was concentration dependent and followed first order kinetics. While the formulations F5 to F9 showed that drug release followed zero order kinetics. Formulation F9 was selected as an optimized one where the drug from immediate layer was released with in15 min and then sustained for a period of 12 hrs. Kinetic treatment to the in vitro release data revealed that the drug release followed zero order non – fickian diffusion with n value greater than 0.45.